Baroque Visions of the Temple of Jerusalem - Michael Rabens (Oz, 1995)
The ancient Jewish temple in Jerusalem has excited interest among artists, architects, and scholars for many centuries. There has been a steady stream of attempts to reconstruct its appearance, despite an overwhelming lack of physical evidence.